2016
DOI: 10.3390/ijerph13010112
|View full text |Cite
|
Sign up to set email alerts
|

Association between UGT1A1 Polymorphism and Risk of Laryngeal Squamous Cell Carcinoma

Abstract: Laryngeal cancer is one of the largest subgroups of head and neck cancers. In addition to smoking and alcohol consumption, genetic polymorphisms are also risk factors for the development of laryngeal cancer. However, the exact relation between genetic variants and pathogenesis of laryngeal cancer has remained elusive. The aim of this study was to examine UGT1A1*6 (rs4148323 A/G) polymorphisms in 103 patients with laryngeal cancer and 220 controls using the high resolution melting curve (HRM) technique and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…These results were similar to previous studies on the expression of DACH1 in esophageal cancer, hepatocellular carcinoma and colorectal cancer [ 10 , 18 , 19 ]. Smoking and alcohol consumption were risk factors of laryngeal carcinoma, and DACH1 increased the risk of laryngeal carcinoma which is consistent with other study [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results were similar to previous studies on the expression of DACH1 in esophageal cancer, hepatocellular carcinoma and colorectal cancer [ 10 , 18 , 19 ]. Smoking and alcohol consumption were risk factors of laryngeal carcinoma, and DACH1 increased the risk of laryngeal carcinoma which is consistent with other study [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…We analyzed gender, age, smoking, drinking, T classification, lymph node metastases, primary location and histopathological differentiation, which were obtained from patient records. Smoking and alcohol consumption were calculated according to [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The primary type is laryngeal squamous cell carcinoma (LSCC), which accounts for 5% of all types of human cancer (2). Tobacco, alcohol and genetic polymorphisms are the main risk factors for the development of LSCC (3). There are three traditional treatments of LSCC: Surgery, radiotherapy and chemotherapy, either alone or in combination (4).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that this null genotype is associated with BC; it has also been suggested that the UGT2B17 enzyme serves a role in cancer drug metabolism (71). Finally, a study reported that smoking or alcohol consumption combined with the G allele of the UGT1A1*6 gene (rs4148323 A/G) increased the risk of laryngeal cancer (27). Further examples of the association between cancer and UGT variants are cited in Table I.…”
Section: Cns Ciotti Et Almentioning
confidence: 99%